Biodiversity of intertidal marine flatworms (Polycladida, Platyhelminthes) in southeastern Australia - Rodríguez, Jorge; Hutchings, Pat A.; Williamson, Jane E. (Zootaxa, 2021)
Flatworms of the Order Polycladida are a group of free-living invertebrates found in a diversity of marine habitats, with over 800 species described worldwide. Marine flatworms are a conspicuous component of Australia’s marine fauna yet have received little attention. Less than 30 scientific articles have been published on Australian marine flatworms since 1855, of which only nine include species from southeastern Australia. Here, the biodiversity and distribution of species belonging to the Order Polycladida inhabiting intertidal rocky beaches in southeastern Australian waters were identified and analysed. Sampling was conducted at low tide along the coasts of New South Wales and Victoria. Collected samples were serially sectioned for comparative anatomical studies, and tissue was removed from each individual for molecular sequencing and analyses. Both nuclear and mitochondrial DNA sequences were obtained and used as an additional source of evidence for the description of new species as well as providing further insight into the phylogenetic relationships between them. A total of 20 species, six of which are new (e.g., Eulatocestus australis sp. nov.), and a new genus (Parabolia gen. nov.) have been described, as well as two new records for Australia (e.g., Stylochoplana clara Kato, 1937) have been identified increasing our knowledge of this important component of the Australian marine biota.